Association of Thyroid Stimulating Hormone With Thyroid Peroxidase Antibody in Apparently Healthy Pregnant Women (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Undiagnosed thyroid disorders have different maternal and fetal adverse outcome. Euthyroid pregnant women with thyroid peroxidase antibody could silently go to overt hypothyroidism, but these can be prevented by identifying the patient with positive thyroid peroxidase antibodies in their early gestation. Objective of the study is to determine the association of serum thyroid stimulating hormone with thyroid peroxidase antibody in apparently healthy pregnant women.Materials and methods: This cross-sectional study was carried out in the Department of Obstetrics and Gynecology, BSMMU between Ist  March 2016 and 28 February 2017. A total of 245 apparently healthy pregnant  women were included in this study. These subjects were tested for Thyroid Peroxidase Antibody (TPO-Ab) serum Thyroid Stimulating Hormone (TSH) and serum Free Thyroxine (FT4).Results: 71(29%) of women at first trimester were found to have TSH > 2.5 and TPO-Ab positive in 54 (22%). Out of these positive subjects 22(30.98%) have raised TSH (>2.5 mIU/L). FT4 was low in 7(3%) of all subjects.  Conclusion: There is a remarkable correlation between TSH and TPO-Ab (p < 0.05) in first trimester of pregnancy. Thus TPO-Ab could be considered as a screening tool.JCMCTA 2023 ; 34 (2) : 62-67